Why Europe? Problems of Culture and Identity
XI, 204 p.
Keywords: This volume addresses a range of issues which underlie the notions of European identity. Among them: what does it mean to be a European? What place will minorities find in the Europe of the twenty-first century? What roles will women play in the future communities? Will Europe become more open to diversity, or become increasingly introspective?